Civil Unrest and Firm Performance: Evidence from Chile - Espinosa-Mendez, C (Oviedo University Press, 2022)
This investigation considers the recent civil unrest in Chile to determine whether these increase or decrease the performance of companies. Using a panel composed of 99 non-financial firms listed on the Santiago de Chile Stock Exchange during the period between the first quarter of 2017 and 2020 I find that civil unrest negatively impacts firm performance. This effect is asymmetric among the different industrial sectors with the Trade and Industrial sectors being the most adversely affected. On the other hand, the Agriculture-fishing and Utilities sectors show a better performance. © 2022, Oviedo University Press. All rights reserved.